The effect of early and late pharmacological correction with GABA derivatives of psychoemotional state of offspring of rats with experimental preeclampsia - Elena A. Muzyko; Valentina N. Perfilova; Kirill V. Suvorin; Ivan N. Tyurenkov (Belgorod National Research University, 2020)
Introduction: Preeclampsia is a serious complication of pregnancy, which increases the risk of anxiety disorders and depression in children at different stages of ontogenesis. Materials and methods: The psychoemotional state of 70-day-old offspring of rats with experimental preeclampsia (EP) was studied after pharmacological correction from the 40th to 70th day of offspring life with GABA derivatives - succicard (22 mg/kg), salifen (7.5 mg/kg), phenibut (25 mg/kg) and comparison drug pantogam (50 mg) - in the Open field test, the Elevated plus maze test, and the Marble burying test. The above mentioned tests, together with the Porsolt test, were performed at the age of 18 months. At the second step, the offspring received succicard (44 mg/kg), salifen (15 mg/kg), phenibut (50 mg/kg) and pantogam (100 mg) from the 24th to 25th month of life. After that, the animals were tested. Results and discussion: The EP progeny had an increased level of anxiety and depression, as well as obsessive-compulsive disorder. Early GABA derivatives exposure limited anxiety and depression in the animals aged 70 days and 18 months, with salifen limiting compulsive behavior. Late GABA derivatives "treatment" exerted anti-compulsive and antidepressant effects, with phenibut having a greater degree of anxiolytic activity. Succicard, salifen and phenibut were comparable or superior to pantogam in terms of effectiveness. Conclusion: EP has a negative effect on the psychoemotional state of offspring. Early and late pharmacological correction with derivatives of GABA, such as succicard, salifen and phenibut, reduced anxiety, manifestations of obsessive-compulsive disorder, and depression in offspring of the rats with EP pregnancy.